An empirical category-ratio scale for evaluating the subjective intensity of noise based on the comparison of estimated magnitudes and categories. (15th January 2020) - Huang, Yu; Li, Dou
Abstract: In psychophysical studies, the methods of magnitude estimation (ME) and rating scale (RS) are often employed to obtain the subjective intensity of noise. Research interest has usually focused on obtaining precise growth functions to express the relation between subjective and objective magnitudes of stimuli in the ME method, or utilising proper categories for a series of stimuli in the RS method. There have been few studies concerned with the validity of the two direct scaling methods in measuring the subjective intensity of noise. This paper investigated the subjective discomfort caused by noise in the methods of relative magnitude estimation (RME), absolute magnitude estimation (AME), and RS. Forty-two participants were divided into three groups, and each group rated the discomfort caused by 22 noise stimuli at sound pressure levels from 49 to 91 dBA using RME, AME or RS method, respectively. Results indicated that the RS method yields interval scales and the ME method yields logarithmic interval scales for the discomfort of noise, so the sensory continua of noise discomfort could be described in linear relation or power function, depending on the evaluating methods. Based on the empirical data, a category-ratio scale was developed for evaluating the noise discomfort by combining the scales of AME and the scales and verbal descriptors of RS. Equations were also proposed tentatively for noise discomfort to predict the categories from the estimated magnitudes.